STUDI TENTANG PENGGUNAAN CYBERCOUNSELING UNTUK LAYANAN KONSELING INDIVIDUAL BERSAMA MAHASISWA PROGRAM STUDI BIMBINGAN DAN KONSELING UNU CIREBON - Nakhma Ussolikhah (Oasis : Jurnal Ilmiah Kajian Islam, 2017)
AbstractThis study was conducted to investigate the study of cybercounseling as an individual counseling service how counselors in providing counseling services through internet technology (CyberCounseling) are able to use based on appropriate techniques, codes of ethics and methods of service use. The student of BK become the primary subject because to see the phenomenon experienced by students is quite problematic so that the need for internet based service or individual counseling. This research is a qualitative, case study whose type is field research (Field research). After exposing the data then compare between the opinions of both. Primary data sources and secondary data.This research departs from the problems faced by students as the final teenage phase in understanding the misuse of the use of information technology that makes problems often experienced as a result of the internet. Through individual counseling students are expected to utilize the usefulness of technology as one of the supporting process of service.The conclusion of this study is that students who often use the internet as a means of communication with lecturers turned out to have a creative value when viewed from the perspective of guidance and counseling. Technology-based services make the primary need for students in the counseling process on campus. With individual counseling through technology then students begin to realize the counseling. The nature of the counseling service is personal, social, learning and career can be developed based on the needs of the counselee.Keywords: Cybercounseling, Individual Counseling